2002
DOI: 10.1177/095162902774006804
|View full text |Cite
|
Sign up to set email alerts
|

A Citizen-Candidate Model with Sequential Elections

Abstract: This article develops a citizen-candidate model with sequential elections. The model highlights the strategic considerations associated with the primary process, which hinge on the preferences of party members, in particular the party medians and the party boundaries. It is shown that although electoral competition leads to convergence in platforms, the primary process limits such convergence. Intuitively, this results from candidates having to please two different sets of citizens in successive races (party m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Early formal modeling-as well as some more recent work-suggested that the presence of primary elections might be pulling parties to the extremes by allowing candidates to be chosen by a less diverse electorate than would be present in the general election (Aranson and Ordeshook 1972;Aldrich 1983;Cadigan and Janeba 2002;Owen and Grofman 2006). But more recent theoretical work has cast doubt on this simple idea.…”
Section: Past Researchmentioning
confidence: 99%
“…Early formal modeling-as well as some more recent work-suggested that the presence of primary elections might be pulling parties to the extremes by allowing candidates to be chosen by a less diverse electorate than would be present in the general election (Aranson and Ordeshook 1972;Aldrich 1983;Cadigan and Janeba 2002;Owen and Grofman 2006). But more recent theoretical work has cast doubt on this simple idea.…”
Section: Past Researchmentioning
confidence: 99%
“…With the utility function specified above, it suffices to assume that c 1 We do not deal with issues of party primaries here. For them, see Cadigan and Janeba [2] and Owen and Grofman [3].…”
Section: The Basic Modelmentioning
confidence: 99%
“…This paper uses a citizen-candidate model (Osborne and Slivinski 1996;Besley and Coate 1997;Cadigan and Janeba 2002;Klumpp 2007) under a plurality election rule. All citizens are potential candidates who simultaneously decide whether or not to become candidates.…”
Section: A Citizen-candidate Model With Violations Of Proximity Votingmentioning
confidence: 99%